2020
DOI: 10.1186/s12879-020-05113-4
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Talaromyces marneffei infection presenting as multiple intestinal perforations and diffuse hepatic granulomatous inflammation in an infant with STAT3 mutation: a case report

Abstract: Background: Talaromyces marneffei is a highly pathogenic fungus that can cause life-threatening fatal systemic mycosis. Disseminated Talaromycosis marneffei affects multiple organs, including the lungs, skin, and reticuloendothelial system. However, T. marneffei infection has rarely been reported in human immunodeficiency virus (HIV)-negative infants with multiple intestinal perforations and diffuse hepatic granulomatous inflammation. Case presentation: We present the case of an HIV-negative 37-month-old boy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…However, there have been few reports of T. marneffei infection in patients with primary immunodeficiency. Pan et al reported that a child with primary immunodeficiency carrying a STAT3 mutation suffered from T. marneffei invasion of the intestinal system, which was characterized by multiple intestinal perforations, erosion, ulcers and polypoid lesions, among other symptoms of intestinal invasion (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been few reports of T. marneffei infection in patients with primary immunodeficiency. Pan et al reported that a child with primary immunodeficiency carrying a STAT3 mutation suffered from T. marneffei invasion of the intestinal system, which was characterized by multiple intestinal perforations, erosion, ulcers and polypoid lesions, among other symptoms of intestinal invasion (19).…”
Section: Discussionmentioning
confidence: 99%
“…In China, most patients with cryptococcosis do not have an immunocompromised status (Ye et al, 2012;Cheng et al, 2021). Talaromycosis marneffei infection, an endemic fungal disease in Asian populations, also occurs in HIV-negative immunocompetent populations (Lee et al, 2019;Pan et al, 2020). Although some patients have been confirmed to have nonclassical immunodeficiency, such as hyper-IgE syndrome and anti-IFN-g autoantibody-associated immunodeficiency syndrome, most patients do not have clear immunodeficiency or hypofunction (Lee et al, 2019;Pan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Talaromycosis marneffei infection, an endemic fungal disease in Asian populations, also occurs in HIV-negative immunocompetent populations (Lee et al, 2019;Pan et al, 2020). Although some patients have been confirmed to have nonclassical immunodeficiency, such as hyper-IgE syndrome and anti-IFN-g autoantibody-associated immunodeficiency syndrome, most patients do not have clear immunodeficiency or hypofunction (Lee et al, 2019;Pan et al, 2020). Due to the lack of specificity in the clinical manifestations of pulmonary mycosis in immunocompetent hosts, mycosis is often not the first consideration during clinical diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies and clinical observations have shown that T.marneffei infection may cause liver damage. While the liver can show different pathological alterations depending on immune status after T.marneffei infection, aspectrum of pathological damage to the liver has been observed in cases of hepatic talaromycosis in some clinicopathological studies [ 15 , 16 ]. However, the specific pathological mechanism is not clear.…”
Section: Introductionmentioning
confidence: 99%